Congress Shall Make No Law: The First Amendment, Unprotected Expression, and the U.S. Supreme Court (AmeriQuests, 2011)
David M. O’Brien’s Congress Shall Make No Law: The First Amendment, Unprotected Expression, and the Supreme Court serves as a significant contribution to the field of First Amendment Law by offering an overview of crucial issues and, moreover, by emphasizing the outlook for the future of free speech. O’Brien’s credentials position him favorably for the task; he was a judicial fellow and research associate with the Supreme Court, he has written numerous articles and books on the Supreme Court, and he is currently the Leone Reaves and George W. Spicer Professor of Law at the University of Virginia. Considering the daunting task of compiling a succinct account and analysis of the history of free speech in the United States, Professor O’Brien does well to allow readers to better understand the complexities of free speech policy in the United States.
Keywords: First Amendment; Freedom of Speech; Freedom of Expression; Supreme Court; Law; Obscenity; Obscene; Free Speech; Definitional Balancing